Hubungan pekerjaan ibu dengan ketepatan waktu, jenis, porsi, dan tekstur pemberian MP-ASI - Masitah, Ravi; Novianty, Novianty (Holistik Jurnal Kesehatan, 2025)
Background: The period of complementary feeding for children aged 6–23 months is a crucial phase for their growth and development. Inappropriate complementary feeding practices, whether in terms of timing, type, portion, or texture, can increase the risk of stunting, malnutrition, and developmental disorders. Maternal employment status is suspected to influence the appropriateness of complementary feeding. Purpose: To determine the relationship between maternal employment and the appropriateness of complementary feeding. Method: This quantitative study used a cross-sectional approach and was conducted in July 2025 in the working area of ​​the 7 Ulu Community Health Center, Palembang, South Sumatra. The sampling technique used purposive sampling with a sample size of 30 participants. The independent variable in this study was maternal employment, while the dependent variable was the provision of complementary feeding. Data were analyzed using univariate analysis with frequency distribution and bivariate analysis with the chi-square test. Results: There was no significant relationship between compliance with complementary feeding and the four variables in this study. This is indicated by the p-values ​​for the variables time (p=0.272), type (p=1.000), portion (p=0.714), and texture (p=1.000), all of which were greater than the 0.05 significance level. Conclusion: There is no significant relationship between maternal employment status and the appropriateness of complementary feeding, either in terms of time, type, portion, or texture (p-value > 0.05).   Keywords: Nutrition; Mother's Occupation; Provision of Complementary Feeding.   Pendahuluan: Periode pemberian makanan pendamping ASI (MP-ASI) usia 6–23 bulan merupakan fase kritis bagi pertumbuhan dan perkembangan anak. Praktik pemberian MP-ASI yang tidak tepat, baik dari segi waktu, jenis, porsi, maupun tekstur, dapat meningkatkan risiko stunting, malnutrisi, dan gangguan tumbuh kembang. Status pekerjaan ibu diduga berpengaruh terhadap ketepatan pemberian MP-ASI. Tujuan: Untuk mengetahui hubungan antara pekerjaan ibu dengan ketepatan pemberian MP-ASI. Metode: Penelitian kuantitatif dengan pendekatan cross sectional, dilaksanakan bulan Juli 2025 di wilayah kerja Puskesmas 7 Ulu Palembang Sumatera Selatan. Teknik pengambilan sampel menggunakan puposive sampling dengan jumlah sampel yang digunakan sebanyak 30 partisipan. Variabel independent dalam penelitian ini adalah pekerjaan ibu, sedangkan variabel dependen adalah pemberian MP-ASI. Analisis data yang digunakan univariate dalam bentuk distribusi frekuensi dan bivariate menggunakan uji chi square. Hasil: Tidak terdapat hubungan yang bermakna antara kepatuhan pemberian MP-ASI dengan keempat variabel dalam penelitian ini. Hal ini ditunjukkan oleh p-value pada variabel waktu (p=0.272), jenis (p=1.000), porsi (p=0.714), dan tekstur (p=1.000) yang seluruhnya lebih besar dari nilai signifikansi 0.05. Simpulan: Tidak terdapat hubungan yang signifikan antara status pekerjaan ibu dengan ketepatan pemberian MP-ASI, baik dari segi waktu, jenis, porsi, maupun tekstur (p-value > 0.05).   Kata Kunci: Gizi; pekerjaan ibu; pemberian MP-ASI.